Problem of Description of the Characteristic Features of Discrimination in the Labor Sphere - A. V. Kychko (Bulletin of Kharkiv National University of Internal Affairs)
The Constitution of Ukraine guarantees the right to labor to everyone, including the possibility to earn one’s living by labor that he or she freely chooses or to which he or she freely agrees. However, discrimination is still one of the main problems in the labor sphere.